Prevalence of OmpK35 and OmpK36 porin expression in beta-lactamase and non-beta-lactamase-producing Klebsiella pneumoniae - Shakib P (Dove Medical Press, 2011)
Pegah Shakib1,2, Sobhan Ghafourian1, Mohammad Reza Zolfaghary2, Reza Hushmandfar3, Reza Ranjbar4, Nourkhoda Sadeghifard11Clinical Microbiology Research Center, Ilam University of Medical Sciences, Ilam; 2Department of Microbiology, Qom Branch, Islamic Azad University of Qom, Qom; 3Faculty of Veterinary Medicine, Ilam University, Ilam; 4Molecular Biology Research Center, Baqiyatallah University of Medical Sciences, Tehran, IranBackground: The aims of this study were to confirm the presence of OmpK35 and OmpK36 in extended-spectrum beta-lactamase-producing and nonextended-spectrum beta-lactamase-producing Klebsiella pneumoniae and to determine the relationship between porin expression and resistance to third-generation cephalosporins.Methods: Fifty-two K. pneumoniae isolates were obtained and analyzed for extended-spectrum beta-lactamase and for OmpK35 and OmpK36.Results: Twenty-two (42.3%) isolates of K. pneumoniae were extended-spectrum beta-lactamase producers. The OmpK35 profile in K. pneumoniae producing extended-spectrum beta-lactamase showed the presence of porin protein in ceftazidime-sensitive K. pneumoniae (six isolates), and the OmpK36 profile in K. pneumoniae producing extended-spectrum beta-lactamase revealed isolates sensitive to cefotaxime (n = 8) and ceftriaxone (n = 6). All nonextended-spectrum beta-lactamase-producing K. pneumoniae showed the presence of OmpK35 and OmpK36 porin proteins.Conclusion: The presence of OmpK35 is mostly related to ceftazidime susceptibility and less to cefotaxime and ceftriaxone susceptibility, while OmpK36 expression is seen more often in cefotaxime-sensitive isolates. OmpK35 and OmpK36 indicate nonextended-spectrum beta-lactamase producing strains, and their presence is important when selecting an antimicrobial agent.Keywords: Klebsiella pneumoniae, extended-spectrum beta-lactamase producing strains, porin expression